Images of Environmental Damage in the Works of Rosario Ferre - Alba, Danielle M. (My University, 2010)
This study examines the texts of Puerto Rican author Rosario Ferre, focusing on her use of imagery and duality to bring awareness to the environmental damge done to the island of Puerto Rico during the industrialization movement. The research focuses on thre of Ferre's works; Papeles de Pandora (The Youngest Doll), Maldito Amor (Sweet Diamond Dust), and La Casa de la Laguna (The House on the Lagoon) with the purpose verifying if the the fiction Ferre writes is historically accurate or if the environmental damage she exposes is unfounded.
Color poster with text and images.
Keywords: Ferre, Rosario--Criticism and interpretation; Environmentalism in literature; Environmental degradation--In literature; Environmental degradation--Puerto Rico; Industrialization--Puerto Rico; Posters